A case study of comparison performance and cost analysis between semi-mechanical and turbo spin spreader in fertilizer application at Johawaki Plantation / Muhammad Safwan Abdul Kahar - Abdul Kahar, Muhammad Safwan (Faculty of Plantation and Agrotechnology, 2016)
Turbo spm spreader and semi-mechanical are the equipment used in fertilizer application (maintenance) in oil palm. Turbo spin spreader give constant rate in shorter time and also reduce labour requirement. Study was conducted to test the performance and cost of using semi-mechanical and turbo spin spreader. Data collected include the time taken during distribution and refill the empty trailer and hooper of turbo spin spreader. Replication was made 2 times in different plot with the same rate per palm. Results showed that the turbo spin had low working hour as 2 hours better than semi-mechanical which use 4 working hours. Effective field capacity for semi-mechanical 3.04 ha/hr and turbo spin 6.1 ha/hr. Labour requirement for semi mechanical is 4 person and turbo spin is 2 operator. The operating cost for turbo spin spreader less than semi-mechanical around RM 7.78 per ha due to low labor cost. Turbo spin spreader can save time and labour cost energy than semi-mechanical to manure the oil palm.